1954
DOI: 10.1136/bmj.1.4877.1455
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cortisone Therapy in Periarthritis of the Shoulder

Abstract: MORTALITY AND SMOKING MDCBRfSH 1455to 20 cigarettes a day) in September, 1951. In another instance, the doctor had described himself as smoking 3j oz. of pipe tobacco a week, but a friend, who signed the death certificate and had known him for 25 years, stated he had previously been one of the heaviest smokers of both cigarrettes and pipe he had ever known. Such factors not only could not produce an exaggeration of the true relationship but must lead to an understatement of it by inflating the mortality among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 1 publication
2
37
0
2
Order By: Relevance
“…Similar results were found in previous studies. 5,6 Even with this high initial dose of oral corticosteroids, however, the short-term results, especially at the 8-and 12-week follow-up, were superior in shoulder scores, range of motion, and patient satisfaction for the intra-articular injection series compared with the oral application program. Widiastuti-Samekto and Sianturi 40 compared oral corticosteroids with a single intra-articular injection.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar results were found in previous studies. 5,6 Even with this high initial dose of oral corticosteroids, however, the short-term results, especially at the 8-and 12-week follow-up, were superior in shoulder scores, range of motion, and patient satisfaction for the intra-articular injection series compared with the oral application program. Widiastuti-Samekto and Sianturi 40 compared oral corticosteroids with a single intra-articular injection.…”
Section: Discussionmentioning
confidence: 85%
“…4,22,32 Oral application of cortisone is also used in the treatment of frozen shoulder syndrome. 5,6,9,10 We hypothesized that oral application of cortisone leads to comparable results and avoids the risk of a joint infection. To our knowledge, no previous studies have compared the results of an intra-articular glucocorticoid injection series with oral glucocorticoid application.…”
mentioning
confidence: 99%
“…One Cochrane review was found concerning the use of oral steroids in the treatment of frozen shoulder, and included five trials (n=179) 14. In three high quality trials1517 oral steroids were compared with placebo or no treatment. No significant differences were found in the short term on pain (no data available)16 and in the long term on pain (RR 0.5; 95% CI 0.1 to 5.1) and ROM (abduction: RR −4.0; 95% CI −14.6 to 6.6) 15.…”
Section: Resultsmentioning
confidence: 99%
“…In three high quality trials1517 oral steroids were compared with placebo or no treatment. No significant differences were found in the short term on pain (no data available)16 and in the long term on pain (RR 0.5; 95% CI 0.1 to 5.1) and ROM (abduction: RR −4.0; 95% CI −14.6 to 6.6) 15. Buchbinder et al 17 found at 3 weeks significant differences in favour of oral steroids for pain (RR 2.7; 95% CI 1.4 to 4.0) and ROM (abduction: RR 23.3; 95% CI 11.3 to 35.5).…”
Section: Resultsmentioning
confidence: 99%
“…Sie schlossen aus ihren Ergebnissen, dass orales Kortison eine signifikante Kurzzeitverbesserung bei "Frozen Shoulder" erreicht. Ähnliche Ergebnisse wurden ebenfalls in anderen Studien gefunden [3,4].…”
Section: Diskussionunclassified